A truck is not a cookie : matching supply with demand at mahindra truck and bus division - Roy, Debjit (London : Indian Institute of Management, Ahmedabad, 2020)
Mahindra Truck and Bus Division (MTBD) is one of India's leading auto industries. Commercial truck brands such as Tata and Ashok Leyland capture a significant portion of the market share. In the case, we discuss the challenges faced by new commercial vehicle players such as Mahindra Truck and Bus in synchronizing supply with demand. The case usually brings out the supply chain nuances associated with trucks, especially from a new entrant's perspective.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Supply and demand -- Case studies; Business logistics -- India -- Case studies